PENGARUH PEMBELAJARAN, KOMITMEN, DAN BUDAYA TERHADAP KINERJA ORGANISASI - Siti Maryam (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
The purpose of this study was to analyze the influence of human resource management practices with several dependent variables including learning, organizational commitment, and organizational culture at PT Enerren Technologies and to overcome the dilemma faced by the organization, namely not achieving organizational performance targets in 2014, 2015, and 2016. The total population is 69 respondents with a total sample of 59 respondents. The sampling method used is probability sampling. The results of this study prove that based on the results of the Simultaneous Statistical Test (F-Test), Organizational Variable Learning (X1), Organizational Commitment (X2), and Organizational Culture (X3) simultaneously have a significant influence on the Organizational Performance variable (Y). Partial Statistical Test results (t-test), Organizational Learning variable (X1), Organizational Commitment (X2), and Organizational culture (X3) partially based on the significant influence on Organizational Performance variable (Y). Therefore, the Management of PT Enerren Technologies Organization is advised to take effective actions to improve the existing performance conditions, through attitudes and policies that are able to improve performance because these variables have the most dominant role in influencing performance improvement.